Search for the critical point of strongly interacting matter (Intermittency analysis by NA61/SHINE at CERN SPS) - Adhikary Haradhan (EPJ Web of Conferences, 2022)
The existence and location of the QCD critical point is an object of both experimental and theoretical studies. The comprehensive data collected by NA61/SHINE during a two-dimensional scan in beam momentum (13A-150A GeV/c) and system size (p+p, p+Pb , Be+Be, Ar+Sc, Xe+La, Pb+Pb) allows for a systematic search for the critical point – a search for a non-monotonic dependence of various correlation and fluctuation observables on collision energy and size of colliding nuclei. In particular, fluctuations of particle number in transverse momentum space are studied. They are quantified by measuring the scaled factorial moments of multiplicity distribution.